Irkutsk’s Quarters: Preamble by the Project Director - Kozmin, Alexei (project baikal, 2015)
The project director Alexei Kozmin speaks about the key principals that were used in the project for the territory in the historical center of Irkutsk: multifunctionality, harmony with man, permeability, careful attitude to history, etc.
Keywords: cultural heritage sites; historical link; preservation of heritage; concept